Optimum fisheries management under climate variability: Evidence from artisanal marine fishing in Ghana - Wisdom Akpalu; Isaac Dasmani; Ametefee K. Normanyo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
In most coastal developing countries, the artisanal fisheries sector is managed as a common pool resource. As a result, such fisheries are overcapitalized and overfished. In Ghana, in addition to anthropogenic factors, there is evidence of rising coastal temperature and its variance, which could impact the environmental carrying capacity of the fish stock. This study investigates the effect of climate variation on biophysical parameters and yields. Our results indicate that the rising temperature is decreasing the carrying capacity. As a result, an optimum tax on harvest must reflect climate variability, as well as the congestion externality.
Keywords: Q22; H21; C61; 330; climate variability; optimal tax; generalized maximum entropy; Ghana; Fischerei; Fischereiressourcen; Klimawandel; Ghana